Day-time-based evaluation of television broadcast in Turkish culture over its approach to public education: Media ethics, corporate social responsibility and some Tv programs - (:unkn) unknown (Sakarya University, 2015)
According to 2012 report of RTÜK (Radio and Television Supreme Council), the following are the daily mean television-watching durations: house wifes watch TV for 4.2 hours a day, retired people watch TV for 4.3 hours a day and the unemployed watch TV for 3.9 hours a day. Television-watching rates are reduced at the weekends. (http://www.rtuk.org : 10) Majority of day-time viewers comprise the house wifes in the community. Families with medium income and lower income turn on the TV as soon as they wake up in the morning as a general attitude and behavior so much so that except for natural disasters, the TV in the house is turned off if a sad event occurs or if someone passes away. The broadcast is naturally cut generally in case of a natural disaster; for example, in case of an earthquake mostly due to insufficiency of infrastructure. And in such case, you cannot get informed about the situation that you are experiencing or what is happening to other people. One may not sit and watch TV throughout the day necessarily but the general behavior is that television is always on like a window that is opening up to the world outside as a one-way communication tool even when a person is doing house work. Sometimes this communication may turn into a conversation between two deaf people. A house woman may give an answer to the person talking on TV or to a conversation on TV; she may get emotional by an image on television and talk to herself about that. Majority of women in our society tend to ‘talk to herself’. The communication that house wifes establish with television should be researched in a multidirectional way, statistical data should be collected and analyzed. The purpose of this article is to analyze the responsibility that the sector of television broadcasting takes with regard to public education in the context of media ethics and corporate social responsibility, to make predictions within the diversity of entertainment medium which has developed and changed in the 21st century and to remind the television producers, broadcasters, presenters and announcers the fact that they will strenghten their own future if they take on responsibility and that they will exist the if the society exists and all of these should be considered keeping in mind that house wifes and especially mothers keep television on in their houses or in their neighbors when they go to them. It also aims to make people think that one can help society to develop by contributing to its education and that it might make people happier. © The Turkish Online Journal of Educational Technology.
Keywords: Broadcasting; Corporate social responsibility; Ethical Intelligence; European Broadcasting Union; Individual ethics; Media ethics; Public education; Public service; Public service; Radio and television supreme council; Television; Turkish culture